Diskursus Fatwa MUI No. 83 Tahun 2023 Tentang Dukungan Terhadap Palestina dan Seruan Boikot Produk Pro-Israel: The Discourse on MUI Fatwa No. 83 of 2023 Regarding Support for Palestine and the Call to Boycott Pro-Israel Products - Al Munawar, Faishal Agil; Azmi, Miftahudin; Rohmanan, Mohammad (Direktorat Jenderal Bimbingan Masyarakat Islam, 2024)
Israel’s brutal military aggression against Palestine has resulted in dozens, if not hundreds, of lives. There are around 41,000 fatalities, 97,166 injured victims, and 11,000 people who have not been found. This fact received a strong response from various countries. Solidarity with the suffering of the Palestinian people is carried out by Muslims in Indonesia. The Indonesian Ulama Council responded by issuing Fatwa No. 83 of 2023 concerning support for the struggle for the Palestinian people. One form of support is boycotting products that are affiliated with Israel. This fatwa is worth studying more specifically, because there are pros and cons that follow. Those who support it call the fatwa a concrete step in support of Palestine. Meanwhile, those who oppose it say the fatwa will result in a decrease in production and lead to threats of layoffs. This article includes empirical research with qualitative methods in the form of describing the data researched and analyzed, and presented in the form of descriptive text. The research results prove that there are several fastfood restaurants in Malang that were affected by the fatwa. One of the effects is decreasing production and laying off employees. If this fatwa is analyzed using Jasser Auda’s maqāṣid syarī’ah, it only has a correlation with the cognitive aspect, while it conflicts with the other five aspects.